ANALYSIS OF THE FLORA OF RESIDENTIAL AND TECHNOGENIC AREAS OF GROZNY CITY - M. Kh. Alikhadzhiev; R. S. Erzhapova (Юг России: экология, развитие, 2014)
Abstract. The process of territorial expansion of the city is accompanied by intensive construction of industrial and social facilities, road network is actively developed, that leads to the transformation of natural vegetation, the appearance of manmade habitats which are actively colonized by segetal-ruderal species.Aim of the work is inventory of flora of disturbed habitats and the study of its current state, identify the taxonomic composition of phytocenoses.Field works were carried with help of route-floristic method in different growing seasons 2010-2012., technogenic and residential area of the city were studied.According to research a list of vascular plants of disturbed habitats numbering 237 species was compiled. Biomorphological and geographic structure is showed, adventive and indigenous flora fraction is determined.